The presence of a low lying pubic tubercle in patients with indirect inguinal hernia - Thomas, Ashwin Aby; Prasad, Amrita; Mahadevan, D. S. A. (International Surgery Journal, 2018)
Background: Among all external abdominal hernias, inguinal hernia is one most commonly encountered. Factors like chronic cough, constipation, prostatic enlargement etc. contribute to its development. Various defensive mechanisms of the inguinal canal like shutter and slit valve mechanisms help prevent its formation. In this study, a comparison has been made between the anthropometric measurements of the pelvis in patients with and without indirect inguinal hernia to look for a statistically significant difference in the position of the pubic tubercle which in turn affects the various protective mechanisms. Other measurements such as Height, Weight and interspinal distance have been included to look for positive correlations between the disease and said measurements. Methods: This study was conducted in the General Surgery Department of SRM Hospital, Medical College and Research Centre, Kattankulathur after ethics committee clearance. It is a case control study conducted on 140 consenting patients and meeting the inclusion criteria from March 2016 to August 2017, of which 70 each were patients of indirect inguinal hernia and patients without inguinal hernia. Results: Results developed using SPSS Software show majority of the subjects with a low lying pubic tubercle were inguinal hernia patients. There was also a positive correlation between the ratios of weight and ST length as well as Height and ST length between cases and controls. Conclusions: It can be concluded from this study that factors such as a low lying pubic tubercle and other related anthropometric variables predispose patients to develop indirect inguinal hernia.